2014
DOI: 10.1021/jp504518g
|View full text |Cite
|
Sign up to set email alerts
|

Not Only Oxidation of Cardiolipin Affects the Affinity of Cytochrome c for Lipid Bilayers

Abstract: Fluorescence quenching of lipid-bound pyrene was used to assess the binding of cytochrome c (cyt c) to liposomes that mimic the inner mitochondrial membrane (IMM) POPC/DOPE/TOCL, with the conditions that it did or did not contain oxidized phosphatidylcholine molecules, i.e., 1-O-hexadecyl-2-azelaoyl-sn-glycero-3-phosphocholine (PazePC), or a mixture of two hydroperoxide isomers derived from POPC (POPCOX). The binding isotherms reveal two dissociation constants, K(D)(1) and K(D)(2), representing, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…Different features observed in the FTIR spectra at pH 2 and 6.5 warrant that CL was not totally protonated at pH 6.5. Even in liposomes with mixed lipids, in the absence of proteins, cardiolipin forms domains (Kawai et al, 2014b) and is reasonable to consider that singly and doubly unprotonated CL molecules may be present in these lipid bilayers. In Figure 2, the organization of CL as vesicles, at pH 6.5 is indicated by the sharp band peaking at 1,732 cm −1 with a shoulder at 1,718 cm −1 that is assigned to the C=O ester group.…”
Section: Resultsmentioning
confidence: 99%
“…Different features observed in the FTIR spectra at pH 2 and 6.5 warrant that CL was not totally protonated at pH 6.5. Even in liposomes with mixed lipids, in the absence of proteins, cardiolipin forms domains (Kawai et al, 2014b) and is reasonable to consider that singly and doubly unprotonated CL molecules may be present in these lipid bilayers. In Figure 2, the organization of CL as vesicles, at pH 6.5 is indicated by the sharp band peaking at 1,732 cm −1 with a shoulder at 1,718 cm −1 that is assigned to the C=O ester group.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that one of the main events of apoptosis is the detachment of cytochrome c from mitochondria, Kawai et al demonstrated that lipid oxidation and reorganization within the membrane change the binding of cytochrome c to liposomes that mimic the inner mitochondrial membrane (IMM). That is, in the presence of 1-palmitoyl-2-azelaoyl- sn -glycero-3-phosphocholine (PazePC), which bears a nonreactive carboxylic group, the dissociation constant between cytochrome c and IMM was increased, while in the presence of a mixture of two hydroperoxide isomers derived from 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC), which have a reactive peroxide group, this same dissociation constant was lowered [ 59 ].…”
Section: Biological Targets Of Photooxidationsmentioning
confidence: 99%
“…Relatively few studies regarding the possible compartmentalization of inner membrane mimicking only-lipid systems have been performed. In some of these, experimental strategies based on epi-, confocal and two photon excitation fluorescence microscopy techniques have been employed to study the lateral structure of membranes using giant vesicles as model systems [ 80 , 100 , 139 , 140 , 141 ].The most common approach relies in the partition properties of particular fluorescent probes into the possible coexisting lipid domains ( Figure 10 : for experiments A, B, C and E) where the fluorescence intensity images obtained will be limited to information about the lipid domain’s shape and size. In the case of Laurdan labeled membrane ( Figure 10 : experiment D), local physical properties of the possible lipid domains were used to associate their presence with equilibrium thermodynamic phases.…”
Section: The Intricate Link Between Lipid Composition and Cristae Organization Revealed By Minimal Model Systemsmentioning
confidence: 99%
“…In the case of Laurdan labeled membrane ( Figure 10 : experiment D), local physical properties of the possible lipid domains were used to associate their presence with equilibrium thermodynamic phases. In the experiments presented in Figure 10 E,F, phase contrast imaging allows to follow the GUV morphology [ 140 , 142 ]. As it can be seen in the left panel of Figure 10 , for some IMM-mimicking lipid compositions, the fluorescent probe used is homogeneously distributed throughout the membrane, and no mesoscopic domains are observed.…”
Section: The Intricate Link Between Lipid Composition and Cristae Organization Revealed By Minimal Model Systemsmentioning
confidence: 99%